If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n + -26 = 18n Reorder the terms: -26 + 5n = 18n Solving -26 + 5n = 18n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-18n' to each side of the equation. -26 + 5n + -18n = 18n + -18n Combine like terms: 5n + -18n = -13n -26 + -13n = 18n + -18n Combine like terms: 18n + -18n = 0 -26 + -13n = 0 Add '26' to each side of the equation. -26 + 26 + -13n = 0 + 26 Combine like terms: -26 + 26 = 0 0 + -13n = 0 + 26 -13n = 0 + 26 Combine like terms: 0 + 26 = 26 -13n = 26 Divide each side by '-13'. n = -2 Simplifying n = -2
| 3x^2=20x+4x^2 | | sqrt(4x-1)+3=0 | | 3(m-3)=4(m+3) | | 9-5x=-30 | | (10/x)=35/(x-5) | | 10/x=35/(x-5) | | 9x+7y=50 | | -3b+5b+7=-9 | | 93.96=4.7+8.7p-2.6p | | 4(7x-8)=-4 | | x-8x=49 | | 5/4m=1/4 | | 5y+6=35 | | x+11/x^2-49x | | 1/3=5/7+y | | 13+7(2x+1)=4x+10 | | 6(-6x-7)=138 | | 4/7n=12 | | -6(4+6x)=-276 | | 5/6t=15 | | 5(x+2)=-12 | | 7(6+4x)=322 | | 4x+3=2x-7+x | | 7.5m=-60 | | 10x-4=9x+17 | | 3(2a-4)=-12 | | 4x^2-x/2x-1=9 | | 8.5y=-59.5 | | -2x-3x=-25 | | 2(-10-3x)=-38 | | 2(-2)2=8 | | 2/9m=6 |